OPTIMIZATION OF SOMATIC EMBRYOGENESIS CULTURE MEDIUM INDUCTION IN COTTON (Gossypium hirsutum L. CV. Y331B-R5) GROWTH IN CÔTE D’IVOIRE - Affoué Sylvie Rachelle, N’GUESSAN; Koutoua, AYOLIE; Yao Kouakou Francois, KONAN; Sopie Edwige Salomé, YAPO; Yatty Justin, KOUADIO; Tanoh Hilaire, KOUAKOU (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
The development of an efficient protocol for somatic embryogenesis in cotton is an essential prerequisite for the adoption of genetic techniques transformation for varietal improvement. The present study aims to evaluate the responses to somatic embryogenesis of the Y331B-R5 cotton variety widely grown in Côte d’Ivoire. For this purpose, the hypocotyl of the vitroplants was used as an explant to initiate friable callus, which is used for the induction of somatic embryos. The effect of the medium compound on somatic embryogenesis was evaluated. For this purpose, four carbon sources (maltose; sucrose; fructose and glucose) at 30 g.L-1 were tested. Then, the effect of different concentrations (20; 30; 40 and 50 g.L-1) of the best carbon source was evaluated. Then, four amino acids (glutamine; casein hydrolysate; glycine and asparagine) were tested. Finally, phytohormones were added to induce embryos. The results showed that glucose at 30 g.L-1 induced the highest level of embryogenic cells (67.34 %). Amino acids tests showed that glutamine (0.5 mg.L-1) was more beneficial (47.31 %). Finally, hormones combination (0.1 mg L-1 2,4-D + 0.5 mg L-1 KIN) induced the highest rate (74.25 %). The MIE medium + 30 g.L-1 glucose + 0.1 mg L-1 2,4-D + 0.5 mg L-1 KIN was the most effective for the induction of somatic embryogenesis in Y331B-R5.